SLITLESS DIGITAL TV SPECTROPHOTOMETER OF THE CRIMEAN ASTROPHYSICAL OBSERVATORY - Abramenko, A. N.; Okhmat, N. N.; Prokof'eva, V. V.; Sharipova, L. M. (Одеські астрономічні публікації, 2017)
The original slitless spectrograph are created in the Crimean Astrophysical Observatory for 0.5-m meniscus telescope. It has three replaceable transparent diffraction gratings with the distance control. The highsensitive TV tube intensified isocon is used as detector. The digital videodata are collected in the memory of the computer PC AT 286. The spectrophotometric observations may be done in wave range of 3700-7400A with spectral resolution 80A, 60A, 30A. Exposure time for stars 10 — 12m is 2-5 minutes. The relative photometric accuracy of one such record is about 3-5%. Absolute photometric accuracy is comparable with it because the artificial photometric standard used for absolute calibration of records.